Quantifying CO2 in apatite by multiple unpolarized transmission FTIR analyses - Zhide Pu; Zhuoran Zhang; Xinjian Bao; Weiran Li; Xi Liu (Solid Earth Sciences)
CO2 is a key volatile component in various fluids and magmas, and apatite is an ideal mineral for constraining the abundance, distribution and behavior of CO2 in different materials of the Solar System. In sharp contrast to water, CO2 in apatites has not been routinely investigated mainly due to lacking user-friendly analytical technique. Here we have developed a user-friendly analytical technique. By a Durango apatite crystal with a CO2 content of ∼277 (44) wt ppm, we performed 17 successful unpolarized transmission FTIR analyses on its randomly-selected fragments with unknown orientations. These analyses well reproduced the CO2 content, attaining a relative difference of ∼9 % only. Simple calculations carried out with this dataset suggest that as the number of the analyses increases from one, the accuracy of the result nonlinearly increases, being very fast at the first few analyses and much slower afterwards. Consequently, there are different minimum numbers of the analyses to meet different degrees of accuracy which may be required by different studies: it is highly unlikely to reach a result of any good by conducting one analysis only, but generally possible to arrive at a result with acceptable accuracy by performing two or three analyses, and almost certain to obtain a good result with high accuracy by collecting four or five analyses. If 10 or more analyses are possible, the accuracy of the result can be exceedingly high, with an absolute relative difference of < ∼10 %. With this user-friendly new method employing multiple unpolarized transmission FTIR analyses on randomly oriented crystals, quantifying CO2 in tiny apatite grains in different terrestrial and extraterrestrial materials can be readily actualized.